PENGEMBANGAN INSTRUMEN TES KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI RELASI DAN FUNGSI - Ramuna Maysa; Kartini; Nahor Murani Hutapea (Jurnal Ilmiah Matematika Realistik, 2026)
The purpose of this study was to develop a mathematical communication skills test instrument on the topic of relations and functions that meets the criteria of validity, reliability, appropriate difficulty level, and good discriminating power. The development process employed the Tessmer model, which consists of the preliminary stage and formative evaluation stage. The preliminary stage involved needs analysis and instrument design, while the formative evaluation stage included self-evaluation, expert review, one-to-one evaluation, and field testing. The instrument, which had been validated by experts and analyzed based on students’ responses, was subsequently administered in field trials involving 30 students for Package I and 30 students for Package II. The final product consisted of 14 test items, all of which were validated by experts and proven capable of measuring students’ mathematical communication skills, particularly in the content area of relations and functions. The results indicated that all 14 items were valid, with reliability coefficients of 0.91 for Package I and 0.83 for Package II. The final instrument comprised 3 difficult items and 11 moderately difficult items, while the discrimination indices ranged from good to very good categories. Based on these findings, the developed instrument is considered feasible and appropriate for use as a tool to assess students’ mathematical communication skills.